The Development of Group Guidance Service Model to Increase The Competence Of Counselor Candidate - Aryani, Farida; Bakhtiar, Muhammad Ilham (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
The group guidance service model is one of the solutions done to increase the competence of counselor candidate, as the model will help students to know their self to be better.  This service guidance is done by designing a program, implementing, evaluating, grasping the concept, and doing an assessment. The purpose of this study is to develop group guidance service model which can be accepted by the students to escalate the competence of counselor candidate. Another goal is to know the effectivity of the model in increasing the competence of counselor candidate. The type of this study is research and development by using development strategy model. The development cycles consist of product development, testing the product, revising, retesting, and re-revising until the product is considered proper to be used.  Based on the study result, we can conclude that group guidance service model is acceptable, appropriate to be used, and useful to help in increasing the competence of counselor candidate. It is proven based on the sig value by comparing data of pre-test and post-test. The sig value (0.000) is lower than the standard (0.05). Therefore, there is significant influence between group guidance service model in increasing the competence of counselor candidate.